Application of the Self Organized Learning Environment Learning Model in Mathematics Learning Arithmetic Sequence Material - Jordan Lompoliuw; Ichdar Domu; Santje M. Salajang (Departement of Mathematics Education, 2024)
The objective of this study is to analyze the disparities in the mean learning achievements between students who utilize the SOLE learning model and those who employ the direct learning model for arithmetic sequence material at Tondano State Vocational School. The research employed a quasi-experimental design with a Posttest Only Control Group Design. The participants in this study consisted of students from class X OTKP 1, who were assigned to the experimental group, and students from class X OTKP 2, who were assigned to the control group. The data gathering method involved administering a technical learning outcomes test at the conclusion of the class (Posttest). The data analysis technique employed in this research utilizes tests on data that has undergone normality and homogeneity testing. The t test calculations yielded a t_count value of 2.736, which exceeded the critical t_table value of 1.685. Therefore, the null hypothesis (H_0) was rejected, and the alternative hypothesis (H_1) was accepted. Therefore, it can be inferred that there is a disparity in the mean learning results of students in the Self-Organized Learning Environment (SOLE) instructional approach and the traditional direct learning approach when it comes to arithmetic sequence material.